A Sustainable Electrochemical-Based Solution for Removing Acetamiprid from Water - Nunes de Morais, Alana Maria; Medeiros Araújo, Danyelle [UNESP]; Barbosa Segundo, Inalmar Dantas; Vieira dos Santos, Elisama [UNESP]; Leal de Castro, Suely Souza; Martínez-Huitle, Carlos A. [UNESP]; Fernandes Alves, Janete Jane (MDPI, 2023)
Pesticides are used worldwide in agriculture to prevent insects and other pests that attack plants and their derivatives. Acetamiprid (ACT) is a type of insecticide belonging to the chemical group of neonicotinoids, which are widely used in agricultural planting to replace organophosphates. Therefore, in this work, the performance of the electrochemical oxidation (EO) process as an alternative solution to eliminate pesticides in water was evaluated. A dimensionally stable anode (DSA, TiO2-RuO2-IrO2) and boron-doped diamond (BDD) were tested as anodes for degrading ACT (30 and 300 mg L−1) by using different applied current densities (j): 30, 60, 90, and 120 mA cm−2. The degradation process was monitored by using ACT decay, spectrophotometric analysis, and chemical oxygen demand. The results clearly showed that ACT (30 mg L−1) was only eliminated from water at the DSA electrode when 90 mA cm−2 was applied, reaching higher removal efficiencies after 180 min of electrolysis. Conversely, ACT was quickly removed at all applied current densities used, at the same concentration. On the other hand, when the ACT concentration was increased (300 mg L−1), 71.4% of the COD removal was reached by applying 90 mA cm−2 using BDD, while no significant improvements were achieved at the DSA electrode when a higher concentration of ACT was electrochemically treated.
Keywords: acetamiprid; electrochemical oxidation; pesticide; wastewater treatment